Salivary secretory leukocyte protease inhibitor (SLPI) and head and neck cancer: The Cancer Prevention Study II Nutrition Cohort. (April 2016) - Pierce Campbell, Christine M.; Giuliano, Anna R.; Torres, B. Nelson; O'Keefe, Michael T.; Ingles, Donna J.; Anderson, Rebecca L.; Teras, Lauren R.; Gapstur, Susan M.
Highlights: Pre-diagnostic salivary SLPI was higher among HNSCC cases than controls. Among cases, salivary SLPI was positively associated with cigarette smoking. Among never smokers, high salivary SLPI was not associated risk of HNSCC. Among smokers, high SLPI was associated with a significantly higher risk of HNSCC. Summary: Objectives: Secretory leukocyte protease inhibitor (SLPI) is an innate-immunity protein displaying antimicrobial and anti-inflammatory properties that is found in high concentrations in saliva. The role of extracellular salivary SLPI in head and neck squamous cell carcinoma (HNSCC) remains unclear. Thus, we aimed to evaluate the association between SLPI and HNSCC risk in the Cancer Prevention Study II Nutrition Cohort. Materials and methods: Among 53, 180 men and women with no history of cancer who provided an oral rinse between 2001 and 2002, 60 were subsequently diagnosed with incident HNSCC between specimen collection and June 2009. In this nested case-control study, archived oral supernatants were evaluated using the Human SLPI Quantikine ELISA Kit for all 60 cases and 180 controls individually matched on gender, race, date of birth, and date of oral rinse collection. Conditional logistic regression was used to estimate HNSCC risk. Results: Overall, pre-diagnostic salivary SLPI was associated with a non-statistically significant higher risk of HNSCC (OR = 1.6, 95% CI = 0.9–3.0). Among never smokers, high SLPI was associated with a non-statistically significant lower risk (OR = 0.5, 95% CI = 0.1–1.9), whereas among ever smokers, high SLPI was associated with a statistically significant higher risk (OR = 2.1, 95% CI = 1.0–4.3) of HNSCC, compared to low SLPI. Conclusion: While results from this study suggest that higher concentrations of salivary SLPI might increase the risk of HNSCC among ever smokers, more research is needed to verify these findings and define the mechanisms by which SLPI and smoking influence the etiology of HNSCC.